SERS‐Enabled Lab‐on‐a‐Chip Systems. Issue 5 (23rd January 2015) - Huang, Jian‐An; Zhang, Yong‐Lai; Ding, Hong; Sun, Hong‐Bo
<x xml:space="preserve">Abstract</x> Surface‐enhanced Raman spectroscopy (SERS) has been combined with microfluidic Lab‐on‐a‐Chip (LoC) systems for sensitive optofluidic detection for more than a decade. However, most microfluidic SERS devices still suffer from analyte contamination and signal irreproducibility. In recent years, both the microfluidics and SERS communities have developed their own solutions that are complementary to each other; their combination even has potential for commercialization. In this review, the recent advances in both fields are summarized with regard to the development of reliable multifunctional SERS‐enabled LoC systems and their broad applications. Starting from SERS fundamentals, reproducible SERS substrates and dynamic microfluidic trapping are discussed. Based on their combination, on‐chip applications beyond SERS are presented, and insight can be gained into the commercialization of portable SERS chips.